Conference Report: High-resolution MS in drug discovery and development: current applications and future perspectives. (March 2012) - Weston, Daniel J; Weidolf, Lars
The evolving use of high-resolution MS (HRMS) across the pharmaceutical industry has seen its integrated application into both quantitative and qualitative assays. Through an American Association of Pharmaceutical Scientists (AAPS)/ American Society for Mass Spectrometry (ASMS) workshop, held at AAPS, key scientists from world pharma discussed the feasibility of this new paradigm shift through examples and visions for the future, assessing impact on drug discovery and drug development, as well as educating users new to HRMS in the field. This report details selected talks from the 2-day workshop, with particular emphasis on their impact, as well as personal conclusions around certain topics.